STUDENTS’ PERCEPTION OF USING ENGLISH SONGS FOR LISTENING COMPREHENSION AT EIGHT GRADE IN SMPN 01 DAU MALANG - Fara Mufrida (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2022)
Abstract: This research presents the students’ perception of using English songs for listening comprehensionThis study aimed to investigate and describe the students’ perceptions of using English songs for listening comprehension, at the eighth grade students of SMPN 01 Dau Malang. The design of this research is descriptive qualitative research. The participants of this research are the eighth grade students of SMPN 01 Dau Malang in 2022 academic year, which consisted of 30 students. To know the students’ perception of using English songs for listening comprehension, questionnaire and interview were used as the instruments for collecting data. The instruments are adapted from Pitaloka (2019), by considering on three aspects which include: students’ perception of using English songs, the benefit or advantages of using English songs for listening, and the challenges of using English songs for listening comprehension. The process of data analysis included data reduction, data display, and conclusion drawing and verification. The findings of this study showed the students’ perceptions of using English songs for listening comprehension were positive in some aspects such as the students felt enjoy, happy and fun in learning listening using English songs. Besides, the students can improve and develop several English skills, especially listening, vocabulary and pronunciation skills. Most students also felt easy to understand the meaning content in the songs. Just a few of students stated that they were difficult to understand the message meaning in the songs. In addition, English songs in learning listening process also made them difficult to concentrate because they friends were noisy.Keywords: Students’ Perception, English songs, Listening Comprehension